Penatalaksanaan Fisioterapi Pada kasus Post ORIF Metacarpal IV Sinistra dengan modalitas Infra Red(IR) dan Terapi Latihan - Puspitasari, Layli; Yunita, Rima; Luklukaningsih, Zuyina (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
Based on 2018 Riskesdas data, an average of 92,976 fractures occurred, totaling 5,144 people. A single trauma and sudden excess force can cause a fracture. Orif installation is carried out if the use of close reduction/plaster fails, Orif is installed on the right fracture fragment. In solving problems in post-orif cases, physiotherapy plays a role in restoring movement and function using infrared modalities and exercise therapy. The energy produced by IR can be absorbed by superficial tissue with a warm feeling, thereby reducing pain. Exercise therapy using active and passive body movements can increase the range of motion of joints, increase muscle strength values ​​to restore functional ability. This research method uses a case study of physiotherapy management in Post Orif Metacarpal IV cases with Infra Red (IR) and Exercise Therapy. Results were obtained such as pressure pain from T0:3 decreased to T6:1, movement pain T0:5 decreased to T6:1. The muscle strength value of left wrist flexor T0:3 increased to T6:5, extensor T0: 3 increased to T6: 5 in left wrist flexor T0: 3 increased to T6: 5, extensor T0: 3 increased to T6:4. Left wrist joint range of motion from T0 (S: 20°-0°-15°) increases to T6 (S: 50°-0°-50°) at T0 left mcp (S: 10°-0°-20°) increases to T6:(S:45°-0°-40°), functional activity from T0:(severe dependence) increases to T6:(light dependence). Being more careful in activities and not pushing your abilities can reduce the incidence of fractures.